(untitled) (Docentes 2.0 Journal, 2024)
The normalization of violence has taken a dangerous course in the history of humanity and has diversified into different forms that are sometimes almost invisible. The objective was to determine the impact of the workshops on the prevention of sexual violence and the promotion of a culture of peace. The study was based on the action research method, humanistic paradigm, qualitative approach, phenomenological design, explanatory and cross-sectional type. With a population of 25 adolescents and young people between 14 and 28 years old, the research is developed through workshops to raise awareness and strengthen leadership skills, using focus group techniques and interviews. The results showed improvements in leadership skills, nonviolent communication, and tools for violence prevention. Additionally, the study incorporated an analysis from neuroscience, revealing both the functional and structural benefits of leadership training to the participants’ brains, particularly in their interpersonal and family relationships. In conclusion, the research showed that leadership training in adolescents and young people can generate positive changes in their behavior, in addition to contributing to the prevention of sexual violence and the promotion of a culture of peace.